Building didactic content repositories: method and tools - Jacek Marciniak (Center for Open and Multimedia Eduacation of the University of Warsaw, 2012)
The article presents the method and tools which allows to build repositories of didactic materials in SCORM using UCTS taxonomic system and Content Repository software. SCORM is a universal specification designed to create reusable materials in digital format. UCTS is a taxonomic model which allows to attribute didactic interpretations to content components. Content Repository is a web software designed to create, store and process didactic content in SCORM. The method was verified while creating E-archeology Content Repository which stores e-learning materials on protection and management of archeological heritage. The repository contains approximately 4500 Learning Objects in 5 languages and about 800 components of didactically useful e-learning components described in UCTS.